Assessing vitamin D levels in an anti-DFS70 positive population: New insights emerging - Teresa Carbone; Vito Pafundi; Nicola Bizzaro; Maria Infantino; Maria Carmela Padula; Angela Anna Padula; Salvatore D'Angelo (Taylor & Francis Group, 2020)
Background: Anti-dense fine speckled 70 (DFS70) autoantibodies have more often been described in apparently healthy individuals than in patients with systemic autoimmune rheumatic diseases (SARD). The aim of this study was to explore the link between anti-DFS70 autoantibodies and vitamin D (25(OH)D) levels in an Italian adult cohort. Methods: Serum samples from 34 (five males and 29 females) anti-DFS70 positive patients (index cases), 34 ANA-negative healthy controls, 34 ANA-positive anti-DFS70 negative SLE patients, both groups age- and gender-matched with the index cases, 23 ANA-positive anti-DFS70 negative healthy blood donors and six female SARD patients showing mixed DFS positive pattern were collected and tested for 25(OH)D levels. Relevant demographics and lifestyle practices, body mass index (BMI), comorbidities, and use of medication were recorded for patients and healthy controls. Results: Mean serum levels of 25(OH)D were significantly higher in anti-DFS70 positive subjects (mean ± SD: 22.1 ± 9.8 ng/ml) than in ANA-negative healthy controls (mean ± SD: 17.3 ± 6.7 ng/ml; p = .03), ANA-positive healthy controls (mean ± SD: 15.2 ± 6.8 ng/ml; p = .01), SLE patients (16.6 ± 11.0 ng/ml; p = .01) and in patients with SARD (15.0 ± 5.6 ng/ml; p = .01). No statistically relevant differences in BMI, clinical, or demographic parameters were found. Conclusions: Our findings showed higher levels of vitamin D in anti-DFS70 positive subjects than in the controls, which is compatible with the hypothesis of the "benign" nature of anti-DFS70 antibodies.